Christian brethren assemblies responsive to change a comparative study of their features in Australia and North America - Gibbs, Cedric Charles John
Includes bibliographical references.
Submitted in partial fulfilment of the requirements for the degree of Master of Arts by course work and major thesis of William Carey International University through Pacific Colege of Graduate Studies. December 1986 Donated by the author.
Keywords: Brethren movement -- Australia; Change -- Brethren movement